Efficacy of Ingenol Mebutate in the Treatment of Actinic Keratoses: A Pre- and Posttreatment Dermoscopic Comparative Analysis - Carbotti, Mattia (Biomed Res Int, 2018)
Actinic keratosis (AK) is a common skin lesion in adults which usually occurs on chronically photoexposed areas and considered as a precancerous lesion or a superficial squamous-cell carcinoma. Many classifications have been proposed and its diagnosis is generally clinical but, sometimes, its wide variety of presentations can make diagnosis difficult, even among expert observers. The malignant potential of AKs imposes an early diagnosis and treatment in order to reduce morbidity and mortality, and, for the characterization of photodamaged skin, noninvasive diagnostic techniques, such as dermoscopy, have proved to be useful, while multiple therapeutic strategies, lesion-directed versus field-directed therapies, are available for the treatment of AKs. In this study, we evaluated the efficacy of ingenol mebutate for the treatment of AKs, with a particular focus on patients' compliance, correlating it to clinical and dermoscopic grading, pre- and posttreatment, of these lesions. Fifty-two enrolled patients with AKs received treatment with ingenol mebutate gel (0.015% for face and scalp; 0.05% for trunk and extremities) and multiple dermatological evaluations. End points of the study were complete and partial clearance of clinically visible AKs on day 90. All acquired data were recorded and statistical analyses were performed. Univariate and multivariate analyses were used to identify possible predictive factors. We retrospectively analyzed patient-related and lesion-related factors to identify which variables, among age, gender, lesion site, pain, LSR score, and pretreatment clinical and dermoscopic grading, could independently predict the response to ingenol mebutate treatment. Our findings showed that pretreatment dermoscopic grade II represents an independent predictive factor of the efficacy of ingenol mebutate therapy (OR=14.78, 95% CI: 1.83–119.59, P=0.012) and that response rates differ on the basis of the treated anatomical sites (OR=0.16, 95% CI: 0.03–0.85, P=0.031). Data from this study provide evidence that ingenol mebutate gel is an effective treatment for AK, with relative ease of use, short exposure, and rapid resolution of local reactions, benefits contributing to high adherence of this therapy. Moreover, dermoscopic analysis of skin lesions offers more information than clinical evaluation alone and can be helpful in identifying different groups of AKs, thus selecting the adequate therapeutic choice.